THE COVID-19 PANDEMIC EFFECT ON THE DETERMINING CHILLI CROP AGRICULTURAL INSURANCE PREMIUM - Manjaruni, Vivin Aprilia; Purnaba, I Gusti Putu; Budiarti, Retno (PATTIMURA UNIVERSITY, 2022)
Parametric insurance is a type of insurance that contains an agreement related to triggering events between the insurer and the insured determined at the beginning of the contract. The provision that applies if the triggering event occurs is that the insurer (insurance company) is obliged to pay a sum of money (compensation) to the insured. Insurance based on area yield insurance is parametric insurance. Ozaki formulated an agricultural insurance model based on yields in an area called the parametric method. The loss of this method is a probability for crop loss that is in the area under the density function curve when the yield is smaller than the maximum guaranteed yield, but the losses calculated in this method only include losses due to crop failure and do not include losses due to the COVID-19 pandemic. Meanwhile, Susilowati and Gunawan, in their journals, explained that the production level of agricultural products, especially chili crops, during the COVID-19 pandemic, tended to be stable but not with the demand and purchasing power of the people, which significantly decreased. The significant decline in sales made farmers experience huge losses. Considering the COVID-19 pandemic impact, we were interested in formulating yield-based agricultural insurance models of chili crop that calculates the COVID-19 pandemic risk. So, the premiums rates and premiums obtained are more realistic and can reduce the risk of losses due to the COVID-19 pandemic for farmers, private companies, and the government.